2022
DOI: 10.2196/32095
|View full text |Cite
|
Sign up to set email alerts
|

Migration of an Escape Room–Style Educational Game to an Online Environment: Design Thinking Methodology

Abstract: Background The COVID-19 pandemic outbreak has led to a sudden change in education, closing schools and shifting to online teaching, which has become an enormous challenge for teachers and students. Implementing adequate online pedagogical approaches and integrating different digital tools in the teaching process have become a priority in educational systems. Finding a way to keep students' interest and persistence in learning is an important issue that online education is facing. One possible way t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Studies have shown that the use of EDG in teaching processes improves students' concept perception, increases their active participation, and motivates them to learn in a more interactive environment (Ferrer, Martinez, and Ibáñez, 2020). EDG have the potential to be an effective tool in mathematics teaching due to their interactive nature (Buchori and Sudargo, 2016;Haruna, Abbas, Zainuddin, Hu, Mellecker, and Hosseini, 2021;Hwang, Chien, and Li, 2021;Hayati and Behnamnia, 2023;Yusof and Shahrill, 2021;Aktaş, Bulut and Aktaş, 2022;Videnovik, Vold, Dimova, Kiønig, and Trajkovik, 2022).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Studies have shown that the use of EDG in teaching processes improves students' concept perception, increases their active participation, and motivates them to learn in a more interactive environment (Ferrer, Martinez, and Ibáñez, 2020). EDG have the potential to be an effective tool in mathematics teaching due to their interactive nature (Buchori and Sudargo, 2016;Haruna, Abbas, Zainuddin, Hu, Mellecker, and Hosseini, 2021;Hwang, Chien, and Li, 2021;Hayati and Behnamnia, 2023;Yusof and Shahrill, 2021;Aktaş, Bulut and Aktaş, 2022;Videnovik, Vold, Dimova, Kiønig, and Trajkovik, 2022).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Kuo et al [5] found that combining digital and physical escape rooms improved students' creative thinking and learning motivation. Videnovik et al [51] found that digital escape room-style games could engage students in the learning process and achieve learning outcomes. Mystakidis and Christopoulos [30] found that digital educational escape rooms can potentially enhance cognitive benefits and learning outcomes.…”
Section: Empirical Evidence Of the Impact Of Digital Escape Rooms On ...mentioning
confidence: 99%
“…Overall, the potential of educational escape rooms as an innovative and engaging method for promoting active learning is promising. Several studies suggest that appropriately designed educational escape rooms can increase student motivation and support their interest in learning (Taraldsen et al, 2022;Fotaris & Mastoras, 2019;Veldkamp et al, 2020;Videnovik et al, 2022;Manzano-León et al, 2021;Fotaris & Mastoras, 2022). According to Fotaris and Mastoras (2019), "…educational escape rooms can provide an enjoyable experience that immerses students as active participants in the learning environment."…”
Section: Theoretical Backgroundmentioning
confidence: 99%